Generalization of h-Convex Stochastic Processes and Some Classical Inequalities. (8th August 2020) - Zhou, Hao; Saleem, Muhammad Shoaib; Ghafoor, Mamoona; Li, Jingjng
Abstract : The field of stochastic processes is essentially a branch of probability theory, treating probabilistic models that evolve in time. It is best viewed as a branch of mathematics, starting with the axioms of probability and containing a rich and fascinating set of results following from those axioms. In probability theory, a convex function applied to the expected value of a random variable is always bounded above by the expected value of the convex function of the random variable. In this paper, the concept of generalized h -convex stochastic processes is introduced, and some basic properties concerning generalized h -convex stochastic processes are developed. Furthermore, we establish Jensen and Hermite–Hadamard and Fejér-type inequalities for this generalization.